1. The problem statement, all variables and given/known data Solve each sysytem usiing any method you wish: x2-y2=21 x+y=7 2. Relevant equations x2-y2=21 x+y=7 3. The attempt at a solution I chose to do the substitution method. so i change equation 2 to this: y=7-x and substitute it into the other equation in place of y. so now equation 1 is this x2-(7-x)2=21 so i foil out that part to get x2-(49-14x+x2)=21 now this is where im stuck im not sure what to doo becuase im not sure if the - outside the paranthesis turns everything inside them to the oposite sign? or what?